PENINGKATAN PEMAHAMAN MAHASISWA MENGENAI MAKNA KULIAH DI ABAD 21 DAN STRATEGI AGAR PERKULIAHAN MENJADI MEANINGFULL - Dayurni, Popi; Umalihayati, Umalihayati (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Education has a very broad meaning. The rapid development of technology in the 21st century will change the meaning of education, especially lectures. With the existence of technology such as the internet, knowledge in the form of abstract theories will be very easy to obtain. Then the question arises whether college is important, what is the function of lectures in the 21st century and is college only a requirement for getting a job. However, nowadays there are many successful figures who prove that you don't need to go to college to be successful. College is not a guarantee to be successful in the future. This fact makes lectures no longer have meaning. Where in fact, college is not a requirement to be successful or get a job, college has a broader meaning than that